“THE HUMAN FACTOR” AS A CAUSE OF FAILURES DURING THE TREATMENT OF COWS USING THE OVS PROGRAM AND PROGESTERONE DEVICES - Jaśkowski, Bartłomiej (Translational Research in Veterinary Science, 2023)
In field conditions, vaginal gestagens or the OVS program are used to treat cows with postpartum anestrus, non-pregnant or repeat breeder. The effectiveness of these varies significantly. We assume that some of the failures can be attributed to organizational errors, mostly consisting in insufficient observation of oestrus and incorrect timing of insemination. The aim of the research was to determine: 1) the percentage of cows inseminated at the correct term, 2) the percentage of cows inseminated at a date significantly different from the expected date. In total, 1.026 cows from 12 different herds were used in the study. The animals were classified into two groups. In group I, 458 females received intravaginal progesterone device CIDR (Zoetis – containing 1.38 g P4) for 7 days, while 295 females received the PRID progesterone device (CEVA containing 1.55 g P4). On the day of device removal, a 500 μg i.m. injection of cloprostenol was administered. Cows were inseminated according to heat symptoms. In group II – 273 cows were subjected to the OVS program (i.m. injection of GnRH (Receptal, Intervet), prostaglandin (i.m. injection of 500 μg of cloprostenol (Estrumate, MSD) on day 7 and the same dose like before GnRH on day 9). Females were inseminated 24h after the final GnRH dose. Of the 753 PRID/CIDR cows, 568 (75.4%) showed heat within the expected period, i.e. between 1 and 5 days after removal of the progesterone IUD. Another 43 (5.7%) lost their insert. This group included additional 5 (0.6%) cows which were inseminated on the 6th or 7th day after insertion of the insert. There were 48 cows in total that lost the insert (6.3%; CIDR 7.4% vs. PRID – 4.7%). 137 (18.2%) cows were inseminated more than 5 days after prostaglandin administration. In group II, 117 cows (42.8%) were inseminated within an acceptable time, i.e. up to 3 days after GnRH administration. The remaining females showed estrus > 5 days after P4 or before PG administration – 156 (57.1%). Summing up; after the use of progesterone inserts, ¾ of the cows were inseminated on time. In 1/5 cows, for various, unknown reasons (missing heat, lack of heat, cows were inseminated at a later date. Using the OVS program, about 40% of cows were inseminated on the indicated date. The remaining ones were inseminated too late or much earlier, during the oestrus and ovulation synchronization program. It cannot be ruled out that the moderate effectiveness of hormonal programs is a gross effect of organizational errors and untimely insemination of cows.